(untitled) (Theatrum historiae, 2023)
Neither economic history nor art history can exist today without a consistent interdisciplinary and transdisciplinary approach. Historians of social and economic history must take into account in their research that the commissioning of an architectural or artistic work (not only) in the early modern period is not merely one type of economic investment, but that it represents a distinctive type of human action characterized by its artistic and spiritual value. Art historians, when studying the sources accompanying the commissioning of architectural works, must take note that, on the basis of the same principles, works that are usually perceived as non-art were commissioned in the early modern domain. Interdisciplinary and transdisciplinary research of this type cannot do without the interconnection of economic, social and legal history from the position of historical science, and from the position of art history, the interconnection of art history, cultural history and the history of lifestyle cannot be omitted.